Sex Differences in Percutaneous Coronary Intervention—Insights From the Coronary Angiography and PCI Registry of the German Society of Cardiology. Issue 3 (March 2017) - Heer, Tobias; Hochadel, Matthias; Schmidt, Karin; Mehilli, Julinda; Zahn, Ralf; Kuck, Karl‐Heinz; Hamm, Christian; Böhm, Michael; Ertl, Georg; Hoffmeister, Hans Martin; Sack, Stefan; Senges, Jochen; et al.
Abstract : Background: Several studies have suggested sex‐related differences in diagnostic and invasive therapeutic coronary procedures. Methods and Results: Data from consecutive patients who were enrolled in the Coronary Angiography and PCI Registry of the German Society of Cardiology were analyzed. We aimed to compare sex‐related differences in in‐hospital outcomes of patients undergoing percutaneous coronary intervention (PCI) for stable coronary artery disease, non‐ST elevation acute coronary syndromes, ST elevation myocardial infarction, and cardiogenic shock. From 2007 until the end of 2009 data from 185 312 PCIs were prospectively registered: 27.9% of the PCIs were performed in women. Primary PCI success rate was identical between the sexes (94%). There were no sex‐related differences in hospital mortality among patients undergoing PCI for stable coronary artery disease, non‐ST elevation acute coronary syndromes, or cardiogenic shock except among ST elevation myocardial infarction patients. Compared to men, women undergoing primary PCI for ST elevation myocardial infarction have a higher risk of in‐hospital death, age‐adjusted odds ratio (1.19, 95% CI 1.06‐1.33), and risk of ischemic cardiac and cerebrovascular events (death, myocardial infarction, transient ischemic attack/stroke), (age‐adjusted odds ratio 1.19, 95% CI 1.16‐1.29). Furthermore, access‐related complications were twice as high in women, irrespective of the indication. Conclusions: Despite identical technical success rates of PCI between the 2 sexes, women with PCI for ST elevation myocardial infarction have a 20% higher age‐adjusted risk of death and of ischemic cardiac and cerebrovascular events. Further research is needed to determine the reasons for these differences.